Design, analysis & fabrication of manure cleaning conveyor / Muhammad Atif Darwish Muhammad Akhir - Muhammad Akhir, Muhammad Atif Darwish (2023)
Conveyor systems have been a staple of factories and warehouses ever since the assembly line was invented, moving materials along the manufacturing line or to storage facilities. Conveyor systems can be quite simple, like rolling pin-style conveyor belts that move objects using the momentum created by slopes. A manure cleaning conveyor is a product developed due to the time consumption and human effort required in traditional manure cleaning methods. The low productivity of rabbit farms due to the high time consumption has led to this project which aims to fabricate a manure cleaning conveyor that can remove rabbits' faeces more efficiently in less time. This project intends to design, analyse, and fabricate a manure cleaning conveyor that is more time efficient and cost-effective compared to existing methods of cleaning manure. The expected outcome of this project is a product that can decrease manual labour and shorten the process of cleaning manure. In conclusion, this manure cleaning conveyor will be efficient, consume less time and energy, and raise hygiene standards which will benefit small-scale farmers